Collaboration and Innovation Strategies between Stakeholders in the Management of Water Resources by the Public Works Department - Dian Satriawan; Muammar Khadafie (Manunggal Halim Jaya, 2026)
This study aims to analyze the collaboration and innovation strategies between stakeholders in the management of Water Resources (SDA) by the Public Works Department (PU) through integrated mixed-method design. The case study approach is applied to several Public Works Office units with variations of policies, geographical conditions, and institutional capacity. Qualitative data obtained through in -depth interviews, Focus Group Discussions (FGD), and analysis of policy documents. Thematic analysis is used to identify driving factors and collaboration barriers, as well as the form of innovation applied. Meanwhile, quantitative data is collected through a survey related to the effectiveness of collaboration, water service innovation index, and operational performance indicators, which are then analyzed with multilevel regression to test the linkages between variables, supported by the validity and reliability of instruments. The results showed that multi -vessel collaboration had a significant effect on the effectiveness of natural resource management. Collaborative leadership, clarity of regulations, and inter-actors is the main factor that encourages cooperation. However, the pattern of collaboration is still ad-hoc and has not been supported by formal institutional mechanisms. In terms of innovation, the use of digital technology and sensorization began to be implemented, although constrained infrastructure, technical competence, and bureaucratic resistance. Quantitative analysis confirms that the quality of collaboration is more dominant in improving service performance and water distribution justice, while technology innovation contributes to operational efficiency. Integration of findings through Design-based Research (DBR) produces an implementative strategy in the form of permanent multi-stakeholder forums, regulatory strengthening, co-creation of innovation models, digitalization acceleration, and increasing human resource capacity. Policy recommendations emphasize the importance of monitoring systems based on the main performance indicator (KPI) which includes technical, social and ecological dimensions.